1986
DOI: 10.1021/bi00370a006
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of acylated and deacylated myelin proteolipid protein

Abstract: The effect of covalently bound fatty acid on the conformation of the myelin proteolipid protein has been studied by ultraviolet and intrinsic fluorescence spectroscopy. With dimethyl sulfoxide used as a perturbant, the exposure of Trp and Tyr residues in various mixtures of chloroform-methanol was evaluated by difference spectroscopy of the proteolipid protein (APL) and its chemically deacylated form (d-APL). The fraction of chromophoric groups exposed increased with the proportion of chloroform with 25% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We have previously shown that incubation of isolated PLP with neutral HA results in the quantitative deacylation of the protein (Bizzozero and Lees 1986; Bizzozero and Good 1990). However, prior to assessing the effect of deacylation on myelin structure, it was necessary to determine if treatment of nervous tissue with HA also removes the PLP‐bound fatty acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that incubation of isolated PLP with neutral HA results in the quantitative deacylation of the protein (Bizzozero and Lees 1986; Bizzozero and Good 1990). However, prior to assessing the effect of deacylation on myelin structure, it was necessary to determine if treatment of nervous tissue with HA also removes the PLP‐bound fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate blanks consisting of vesicles without protein were prepared and their absorbances at 450 nm were subtracted out from the sample values. The amount of protein incorporated into vesicles was assessed by the high‐speed centrifugation technique (Bizzozero and Lees 1986). In some experiments, PLP‐induced vesicle aggregation was monitored by light microscopy using a Olympus BX60 Microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quenching of Trp fluorescence in proteins by chloroform has been used to study the location of Trp residues in proteins (8), but to interpret the results of chloroformquenching experiments, it is necessary to appreciate the importance of the photochemical reaction (5). Chloroform has also been used as a solvent for the solubilization of a variety of integral membrane proteins, such as the c-subunit of ATP synthase (9)(10)(11), myelin proteins (12,13) and small multidrug-resistant proteins (14,15). The findings presented here demonstrate that UV illumination of the protein in chloroform-containing solvents may lead to photodestruction of the Trp residues.…”
Section: Introductionmentioning
confidence: 99%
“…In cell‐free systems, PLP is palmitoylated with acyl‐CoA by a nonenzymatic mechanism (Bizzozero et al, 1987), and it is depalmitoylated by a specific fatty acylesterase (Bizzozero et al, 1992). Although the physiological role of the thioesterification cycles and the specific function of the acyl moieties are presently unknown, the removal of fatty acids produces large conformational changes that are thought to affect the biological activity of the protein (Bizzozero and Lees, 1986 a ).…”
mentioning
confidence: 99%